All in One ‐ Complete Issue: ChemInform 48/2016. Issue 48 (10th November 2016) - Unknown
Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading chemistry journals. The following PDF file contains a complete ChemInform issue, thus enabling easy electronic browsing further facilitated by electronic bookmarks.